Childcare Costs and Migrant and Local Mothers' Labor Force Participation in Urban China. Issue 2 (3rd April 2018) - Song, Yueping; Dong, Xiao-yuan
ABSTRACT: This study empirically analyzes the impact of childcare costs on the labor force participation (LFP) and childcare utilization of migrant and local mothers of preschool-age children in urban China, using data from the 2010 National Dynamic Monitoring Survey of Floating Populations. The estimates show that childcare costs have a strong negative effect on the LFP and childcare utilization of migrant and local mothers. Compared to local mothers, the LFP and childcare utilization rate of migrant mothers are, respectively, more and less sensitive to changes in childcare costs. The analysis indicates that the LFP and childcare choices of migrant mothers are more constrained by the lack of access to affordable childcare than are local mothers in China.